Particulate air pollution and survival after stroke in older adults: A retrospective cohort study in Korea - Han, Changwoo; Oh, Jongmin; Lee, Dong Wook; Kim, Soontae; Bae, Hyun Joo; Jang, Yoonyoung; Hong, Yun Chul; Lim, Youn Hee (Environmental Research, 2021)
Although many studies have evaluated the effects of ambient particulate matter with diameters of less than 2.5 μm (PM2.5) on stroke mortality in the general population, little is known about the mortality effects of PM2.5 in post-stroke populations. Therefore, a retrospective cohort was constructed using information from the health insurance database to evaluate whether exposure to PM2.5 is associated with increased mortality in aged stroke survivors residing in seven Korean metropolitan cities. A total of 45,513 older adults (≥65 years) who visited emergency rooms due to stroke and who were discharged alive between 2008 and 2016 were followed up. By using district-level modeled PM2.5 concentrations and a time-varying Cox proportional hazard model, associations between 1-month and 2-month moving average PM2.5 exposures and mortality in stroke survivors were evaluated. The annual average concentration of PM2.5 was 27.9 μg/m3 in the seven metropolitan cities, and 14,880 subjects died during the follow-up period. A 10 μg/m3 increase in the 1-month and 2-month moving average PM2.5 exposures was associated with mortality hazard ratios of 1.07 (95% confidence interval: 1.05, 1.09) and 1.06 (95% confidence interval: 1.03, 1.08), respectively. The effects of PM2.5 were similar across types of stroke (ischemic and hemorrhagic), age groups (65–74, 75–84, and ≥85), and income groups (low and high) but were greater in women than in men. This study highlights the adverse health effects of ambient PM2.5 in post-stroke populations. Active avoidance behaviors against PM2.5 are recommended for aged stroke survivors.
Keywords: Aged; Air Pollutants; Air Pollution; Cities; Cohort Studies; Environmental Exposure; Female; Humans; Male; Particulate Matter; Republic of Korea; Retrospective Studies; Stroke; Cohort study; Mortality; Particulate matter; Stroke; Survival